2010
DOI: 10.1016/j.farma.2009.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Análisis de la efectividad de un protocolo de antiemesis implantado en la Unidad de Oncología

Abstract: The proposed antiemetic protocol is effective for controlling vomiting in chemotherapy regimens with an HL of 1-3. For highly emetogenic regimens, the antiemetic protocol is also effective, but protection is not complete. This protocol seems less effective for controlling nausea, although this is a subjective symptom which is difficult to assess and not routinely measured in clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 16 publications
0
6
0
10
Order By: Relevance
“…Compliance here was 68% and 85%. 19,21 Our patients, whose compliance with treatment was lower (61%), had slightly less protection than these studies.…”
Section: Discussionmentioning
confidence: 58%
“…Compliance here was 68% and 85%. 19,21 Our patients, whose compliance with treatment was lower (61%), had slightly less protection than these studies.…”
Section: Discussionmentioning
confidence: 58%
“…(3) Eff ective treatment reduces morbidity and the risk of complications, and also prevents premature termination of chemotherapy. (4) All chemotherapy drugs have emetogenic potential of diff erent intensities. However, such emetogenic risk does not include nausea.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequent factor related to the ND nausea while undergoing chemotherapy was being younger than 50 years old, which was reported by 14 studies 12 - 13 , 20 - 21 , 23 , 26 - 28 , 30 , 32 , 35 - 38 . Young patients more frequently reported acute and late nausea induced by antineoplastic chemotherapy than older patients in all the treatment cycles 41 , and also reported that these symptoms negatively impacted their daily lives 42 .…”
Section: Discussionmentioning
confidence: 90%
“…Another individual factor was the patient's sex. Nausea was more frequently identified among women than among men 20 - 21 , 23 , 27 , 28 , 30 , 35 - 38 . The same was observed with regard to acute nausea, which affected 48% of women compared to 18% of men, as well as for late nausea, which affected 75% of women versus 51% of men 40 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation